2019
DOI: 10.1016/j.jmb.2019.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of FMN-Binding β-Glucuronidases in the Human Gut Microbiome

Abstract: The human gut microbiota encodes β-glucuronidases (GUS) that play key roles in health and disease via the metabolism of glucuronate-containing carbohydrates and drugs. Hundreds of putative bacterial GUS enzymes have been identified by metagenomic analysis of the human gut microbiome, but less than 10% have characterized structures and functions. Here we describe a set of unique gut microbial GUS enzymes that bind flavin mononucleotide (FMN). First, we show using mass spectrometry, isothermal titration calorime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 17 publications
0
34
1
Order By: Relevance
“…2A, colored triangles). These classes have been described in detail previously (27)(28)(29)(30); briefly, the Loop 1 and mini-Loop 1 enzymes contain active site-proximal loops that provide favorable interactions for binding smaller substrate-glucuronides. The Loop 1 and mini-Loop 1 enzymes are most frequently associated with the cleavage of small-molecule glucuronides, including drug-glucuronide substrates.…”
Section: Identification Of Estrogen Glucuronide-processing Gut Microbmentioning
confidence: 99%
See 3 more Smart Citations
“…2A, colored triangles). These classes have been described in detail previously (27)(28)(29)(30); briefly, the Loop 1 and mini-Loop 1 enzymes contain active site-proximal loops that provide favorable interactions for binding smaller substrate-glucuronides. The Loop 1 and mini-Loop 1 enzymes are most frequently associated with the cleavage of small-molecule glucuronides, including drug-glucuronide substrates.…”
Section: Identification Of Estrogen Glucuronide-processing Gut Microbmentioning
confidence: 99%
“…Third, we modeled the estrogens within the active site of a dimer from Ruminococcus gnavus 3 GUS (6MVG), an FMNbinding GUS (30). We have previously shown that although these enzymes have an open, planar active site with few aromatic residues, they contain roughly 150 residues that have yet to be resolved in any of the crystal structures we have determined to date (30).…”
Section: Structural Rationale For Estrogen Glucuronide-processing Gutmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition. The hundreds of unique gut microbial GUS enzymes mapped to date have been categorized into six functionally distinct groups based on active site architecture (13)(14)(15)(16)(17)(18)(19)(20). GUSs are encoded by Bacteroidetes, Firmicutes, and Proteobacteria; among these phyla, Proteobacteria are unique in encoding only Loop 1 (L1) GUS orthologs, which are most efficient with smaller glucuronidated substrates (14).…”
Section: Gus Loop Architecture Dictates Sn38-g Processing Efficiency Andmentioning
confidence: 99%